Natural Assets and Industrial Transformation in Cross River State: A Political Economy Perspective - Iwara Eno, Iwara,; John Anyabe, Adams,; Sunday, Emmanuel, (IJRDO - Journal of Social Science and Humanities Research, 2017)
This work addresses itself to the fundamental necessity of the utilization of natural assets for industrialization in Cross River State, against the backdrop of the State’s inability to transmute its potential assets to real assets. The work essentially adopted the descriptive procedure of analysis, having collected data from secondary sources. The work situated its argument within a radical political economy context, and articulated the need for government to promote a pumppriming strategy of industrialization in Cross River State. To this end, the work, which dwelled largely on solid mineral assets endowed the State, classified the minerals into seven categories of industries that are possible in the State. The work also accentuates the point that given the rich agricultural land in the State, government should in addition to solid minerals based industries, promote agro-allied industries. Finally, the work avers that the ruling class in the State should shift away from the prevailing rent-seeking behaviour, to a visionary and strategic thinking leadership with imagination to industrialize the State, and that the people in turn, should brace-up to support the expected industrial policy framework of government.